Determination of Potato X-Virus Reservoir Plants by Immunoenzyme Method (Texas Journal of Agriculture and Biological Sciences, 2022)
The importance of natural reservoir plants in the conservation and circulation of phytoviruses in nature is considered to be very high. These reservoir plants in most cases keep the virus at a low concentration and may not show symptoms of the disease, so a very sensitive diagnostic method is needed to detect such latent reservoirs. One of these methods is the enzyme immunoassay method. In this work, natural reservoir plants of Potato Virus X were identified by enzyme immunoassay. As a result of the research, it was found that out of thirty species of cultivated and wild plants, the natural reservoirs of the virus are Cucumis sativus L, Rumex crispus L, Brassica juncea (L) Czern, Althaea officinalis L, Malva neglesta Wall.